Holding Out for a Husband ‘Til the End of the Fast: Wifehood, Widowhood, and Female Renunciation in Two Jain Mahābhārata Adaptations - Simon Winant (Religions)
Among the Dharmic religious traditions, Jainism is unique for its continuous tradition of female monastics. Jain monastic women have made up a large part of Jain communities up to this day. Naturally, their prominent position in Jain society is reflected in the countless depictions of Jain nuns (āryikā/sādhvī) in Jain narrative literature. However, despite Jain narratives sometimes extolling renunciation as an alternative, often even superior, ideal to wifehood, there remains a fundamental tension between the ideologies of normative Jain wifehood and renunciation as well as the question of widowhood. In this article, I explore how two Digambara Sanskrit texts deal with the question of premature widowhood and renunciation in their adaptation of the Mahābhārata narrative. Whereas Jinasena’s Harivaṃśapurāṇa (783 CE) stress the value of pativratā-ideology as an appropriate response for prematurely widowed young Jain women, Śubhacandra’s Pāṇḍavapurāṇa (1552 CE) adapts the exact same episodes, but introduces an explicit ambivalence towards the idea of young Jain women renouncing to become Jain nuns. By comparing these two Digambara adaptations, I wish to show how Digambara Jain narratives in Sanskrit dealt with the same tension between Jain wifehood and renunciation hitherto mostly discussed with reference to Jain narratives in the vernacular.